How Atg18 and the WIPIs sense phosphatidylinositol 3-phosphate - Baskaran, Sulochanadevi (Landes Bioscience, 2012)
The key autophagic lipid sensors are Atg18 in yeast and the WIPI proteins in mammals. Atg18 and the WIPIs belong to the PROPPIN family of proteins. PROPPINs are seven- bladed β-propellers that bind to phosphatidylinositol 3-phosphate (PtdIns3P) and phosphatidylinositol 3,5-bisphosphate [PtdIns(3,5)P2]. In order to understand how PROPPINs bind phosphoinositides, we have determined the crystal structure of a representative, biochemically tractable PROPPIN, Hsv2 of Kluveromyces lactis. The structure revealed that PROPPINs contain two phosphoinositide binding sites which cooperate with a hydrophobic anchoring loop in membrane binding. These three binding elements cooperate in function, as demonstrated by the incremental loss of function in Atg18 mutants impaired in combinations of the two phosphoinositide binding sites and the hydrophobic loop.